(untitled) (Perner’s Contacts, 2011)
Contribution deals with one possible application of image processing - recognition of moving object position. Traced object is robot MINDSTORM NXT, which is described in the first part of the paper. The methodology of image processing and object recognition is discussed in the second part of the paper. The third part describes the application example.